Intradermal testing and serum allergen-specific IgE-testing in cats with naturally occurring feline bronchial disease - Richter, Petra; Stursberg, Ulrike; Pfeiffer, Isabella; Loesenbeck, Gerhard; Sauter-Louis, Carola; Hartmann, Katrin; Mueller, Ralf S.; Doerfelt, Renè; Schulz, Bianka S. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2023)
Objectives While feline asthma (FA) is considered to be of allergic origin, the etiology of feline chronic bronchitis (CB) to date is unknown. Aim of the study was to compare the results of intradermal testing (IDT) and serum testing for allergen-specific immunoglobulin E (SAT) in cats diagnosed with FA and CB.Material and methods Twenty-seven client-owned cats with clinical signs, suggestive of feline inflammatory bronchial disease (FBD) were prospectively enrolled in the study. Patients were assigned to 3 groups based on results of bronchoalveolar-lavage-fluid (BALF)-cytology: FA (n=8), CB (n=10), or cats with a physiological BALF cytology (PB; n=9). A standardized IDT for 27 allergens was performed in all cats. In addition, allergen-specific IgE was measured in serum samples using an FcεRIα-ELISA. The number of positive reactions in both tests was compared between groups, and agreement between test results of both tests was evaluated.Results Regarding the number of positive reactions, no statistically significant difference was detected between groups in IDT (p=0.65) and SAT (p=0.51). When comparing the 2 test systems, a weak correlation was found for the allergens Tyrophagus putrescentiae (k=0.256), Dermatophagoides farinae (k=0.276), and rye (k=0.273). The most commonly observed reactions were to house dust mites, storage mites, rye and nettle in IDT and to sheep sorrel, storage mites, and house dust mites in SAT.Conclusion and relevance IDT and SAT in cats with feline inflammatory bronchial disease (FBD) cannot be used interchangeably for allergen detection. Sensitization to environmental allergens can occur in cats with and without airway inflammation. Therefore, a positive test result should always be assessed in context with clinical signs and allergen exposure.
Keywords: Feline lower airway disease; allergy testing; feline asthma; chronic bronchitis; cough